Instilling Religious Values in Children Through the Role of Parents and Habituation at School - Miftahurrohmah, Linda; Sya’dullah, Achmad; Yani, Muhammad Turhan (Journal of Islamic Education Students (JIES), 2024)
Instilling religious values with the habit of praying, there are still many children who have not been able to get used to this because there is no habit at home and at school regarding good and correct prayer procedures. This research aims to examine the role of parents and the school environment in instilling religious values, especially the habit of praying, in children. The research method used is qualitative literature study. This research uses secondary data sources based on the result of activities carried out by children at school. The observation method is carried out as a guide to provide solutions to problem that occur. The research results show that parents have a crucial role models in teaching and accustoming children to prayer. The school environment also plays an important role by creating an atmosphere that supports the habit of praying through religious the example of teachers. Collaboration between parents and schools is very necessary to create consistency in the habit of praying, both at home and at school. Good communication, consistent support, and joint activities between parents and schools can strengthen the instillation of religious values in children, sgo that children can develop strong and sustainable prayer habits.